2/3x-2=1/6x=3

Simple and best practice solution for 2/3x-2=1/6x=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/3x-2=1/6x=3 equation:



2/3x-2=1/6x=3
We move all terms to the left:
2/3x-2-(1/6x)=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
Domain of the equation: 6x)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
2/3x-(+1/6x)-2=0
We get rid of parentheses
2/3x-1/6x-2=0
We calculate fractions
12x/18x^2+(-3x)/18x^2-2=0
We multiply all the terms by the denominator
12x+(-3x)-2*18x^2=0
Wy multiply elements
-36x^2+12x+(-3x)=0
We get rid of parentheses
-36x^2+12x-3x=0
We add all the numbers together, and all the variables
-36x^2+9x=0
a = -36; b = 9; c = 0;
Δ = b2-4ac
Δ = 92-4·(-36)·0
Δ = 81
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{81}=9$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(9)-9}{2*-36}=\frac{-18}{-72} =1/4 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(9)+9}{2*-36}=\frac{0}{-72} =0 $

See similar equations:

| 6+2b=5b-12 | | 2x+320=930 | | 24=5(u+6)-8u | | O.4x-1.2=0.15x+0.8 | | 2j−1=5 | | -4(1-5n)-8(n+10)=10-2n+n-3 | | 4x-8x+11=17-2x | | 10(x+5)-12=-2 | | x+12/6=8 | | 3x+6(2x-2)=7-4x | | 7r^2+25r^2-12=0 | | 8f+12=7f=9 | | 1x+3=-1-5 | | -x-29=16-4x | | 109=5v+9 | | 4/5n=3/10 | | 10k=-200 | | 2z+7=52-8(2+4) | | 0.08y+420-0.14y=0.88y | | 138+11s=193 | | 7+18m=-4m-15 | | x/2+2=-52* | | 4/3y=9 | | w4− –10=14 | | E(h)=20 | | 6^8x-10=10^3x-4 | | -10x-(-30)+8x=22 | | 4y-2y+12-38=42 | | |x+3|+8=2 | | -2(x+8)=4x-6+2(6x+1) | | -5x+1=-9* | | 7(x+3)+3=73 |

Equations solver categories